Rewriting Conjunctive Queries over Description Logic Knowledge Bases. - Pérez-Urbina, H; Motik, B; Horrocks, I (Springer, 2008)
We consider the problems of conjunctive query answering and rewriting for information integration systems in which a Description Logic ontology is used to provide a global view of the data. We present a resolution-based query rewriting algorithm for DL-Lite∈+∈ ontologies, and use it to show that query answering in this setting is NLogSpace-complete with respect to data complexity. We also show that our algorithm produces an optimal rewriting when the input ontology is expressed in the language DL-Lite. Finally, we sketch an extended version of the algorithm that would, we are confident, be optimal for several DL languages with data complexity of query answering ranging from LogSpace to PTime-complete. © 2008 Springer Berlin Heidelberg.